PENINGKATAN PERILAKU SOSIAL SANTRI MELALUI PROGRAM BANTUAN INFAQ DI PONDOK PESANTREN PUTRI WALISONGO CUKIR DIWEK JOMBANG - Faizatul Muqoddimah; Jumari (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam, Universitas Hasyim Asy'ari Tebuireng Jombang, Indonesia, 2021)
Santri have the characteristics of behaving politely, helping each other and having a noble character. In Islam, every Muslim is recommended to carry out severalpractices that train social behaviour, one of which is by Infaq. Seeing the condition of the students at the Walisongo Cukir Diwek Jombang Islamic Boarding School in Jombang who are not yet good at social behaviour. Therefore, the caregivers of the Walisongo Women's Islamic Boarding School have a program to increase the awareness of students. The research has a purpose to implement and determine the supporting and inhibiting factors of the infaq assistance program, as well as to improve the social behaviour of the students at the Walisongo Cukir Diwek Jombang Islamic Boarding School through theinfaq assistance program. The method in this research is qualitative and descriptive qualitative types. Descriptive research is research that describes existing phenomena, whether engineering or scientific phenomena. This research stage is by interview, observation, and documentation, and checking the validity of the data by triangulation. The results of this study are that students can have a caring attitude, can respect others, increase their sense of help, have good morals and can be more grateful so that they can easily live their daily lives and be accepted in society through the infaq assistance program.